Lower urinary tract symptoms evaluation with uroflowmetry in patients with benign prostatic hyperplasia - Agrawal, Shivendra; N., Srinath; Prathvi; Reddy, Sreedhar; L. N., Raju; Bolbandi, Deepak (International Journal of Research in Medical Sciences, 2024)
Background: Uroflowmetry, a non-invasive urodynamic technique, is commonly employed in evaluating patients with potential lower urinary tract dysfunction. Accurate assessment of the severity of lower urinary tract symptoms (LUTS) can be achieved through the utilization of various validated questionnaires, such as the International Prostate Symptom Score (IPSS). The objective of this study was to investigate the correlation between uroflowmetry parameters and the severity of symptoms. Methods: Fifty patients with LUTS caused by benign prostatic hyperplasia were evaluated by using uroflowmetry, IPSS, prostate volume estimation from May 2022 to December 2023. The correlations between these parameters were quantified by means of Spearman correlation co-efficients. Results: Significant statistical correlations were identified between the IPSS and uroflowmetry outcomes, including peak flow rate, average flow rate, and post-void residual urine. However, no correlation was observed between the IPSS and measurements of prostate volume. Conclusions: A positive correlation was observed between the measured peak flow rate through uroflowmetry and the severity of lower urinary tract symptoms.